Analisis Pesan Dakwah Lagu Tobat Maksiat - Muqoddam Cholil; Kamaliah Kamaliah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
This study aims to determine the meaning of the message in the lyrics of Penance Maksiat. This study is qualitative content analysis techniques. Based on the results obtained, it can be concluded that the percentage of messages provide the creed lyrics Tobat Maksiat reached 34.18%, the message of worship of 21.27%, 20.18% muamalah message and moral message reaches 22.54%. The appreciation of Penance song Maksiat a positive impact on society, especially in vertical relationship to God. When viewed in terms of propaganda methods described in the Quran concluded that the propaganda methods Wali Band included in hasanah mau'izhah method.